IMPLEMENTED READING TECHNIQUES ON READING COMPREHENSION FOR JUNIOR HIGH SCHOOL STUDENTS - Amrina Rosyada (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract: This study aims at determining the effect of reading techniques on readingcomprehension of state Junior High School students in South Jakarta. The implementedreading techniquesareReading Aloud and Silent Reading, which are designed to explorestudents’ natural ability and teachingin reading comprehension, while in silent readingstudents are given a certain amount of time to silently read the selected texts without instructionfrom the teacher and interaction to peers. The experiment takes samples of 39 studentscomprising 20 students for experiment class using the reading aloud, and 19 students forcontrol class using the silent reading. The students’ reading comprehension is measuredquantitatively by using the t-test two tailed to find out the significant difference between theexperimentclass and the control class. Findings provide a significant difference between theimplemented reading aloud in experiment class and the implemented silent reading in controlclass. Therefore.Keywords: reading aloud, silent reading, reading comprehension.